1991
DOI: 10.1099/0022-1317-72-11-2739
|View full text |Cite
|
Sign up to set email alerts
|

Frequent detection of bovine polyomavirus in commercial batches of calf serum by using the polymerase chain reaction

Abstract: Twenty commercial batches of calf serum, obtained from several suppliers, were tested for the presence of bovine polyomavirus (BPyV) DNA and antibodies against the virus. Using polymerase chain reaction (PCR) technology, BPyV DNA was detected in 70% of the batches; no BPyV was detected in any of the negative control samples. The specificity of the amplification reactions was proven by hybridization. PCR results were confirmed by virus isolation experiments performed with five PCR-positive and five PCRnegative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

1992
1992
2010
2010

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…For example, BPV was recovered from tissue cultures and is believed to be a contaminant with the calf serum, but no study we are aware of reported its natural host. Some doubt is cast on the bovid origin of BPV by the lack of correlation between detection of viral DNA by PCR and the presence of virus-specific antibodies in serum (51). Similarly, the natural host of the LPV is not known for certain and serological studies have not been able to address this uncertainty.…”
Section: Discussionmentioning
confidence: 99%
“…For example, BPV was recovered from tissue cultures and is believed to be a contaminant with the calf serum, but no study we are aware of reported its natural host. Some doubt is cast on the bovid origin of BPV by the lack of correlation between detection of viral DNA by PCR and the presence of virus-specific antibodies in serum (51). Similarly, the natural host of the LPV is not known for certain and serological studies have not been able to address this uncertainty.…”
Section: Discussionmentioning
confidence: 99%
“…BPyV sequences have been reported by diverse authors to be found in calf serum batches (24,32,38,39). Although antibodies have been detected in cattle (32,44) and in humans in close contact with cattle (31), no specific illness has been attributed to BPyV.…”
mentioning
confidence: 99%
“…Therefore, BPyV should be considered as one of the tumorigenic polyomaviruses. Since commercial batches of (foetal) calf serum have been shown to be frequently contaminated with this virus (Schuurman et al, 1991 a) it is recommended that cattle sera should be screened for the presence of BPyV prior to use in cell culture.…”
Section: Discussionmentioning
confidence: 99%
“…Foetal calf serum (FCS) used to supplement cell culture media was tested for BPyV prior to use by using the polymerase chain reaction (PCR;Schuurman et al, 1991 a).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation